Cellular and molecular mechanisms of sarcopenia: the S100B perspective. Issue 7 (30th November 2018) - Riuzzi, Francesca; Sorci, Guglielmo; Arcuri, Cataldo; Giambanco, Ileana; Bellezza, Ilaria; Minelli, Alba; Donato, Rosario
Abstract: Primary sarcopenia is a condition of reduced skeletal muscle mass and strength, reduced agility, and increased fatigability and risk of bone fractures characteristic of aged, otherwise healthy people. The pathogenesis of primary sarcopenia is not completely understood. Herein, we review the essentials of the cellular and molecular mechanisms of skeletal mass maintenance; the alterations of myofiber metabolism and deranged properties of muscle satellite cells (the adult stem cells of skeletal muscles) that underpin the pathophysiology of primary sarcopenia; the role of the Ca 2+ ‐sensor protein, S100B, as an intracellular factor and an extracellular signal regulating cell functions; and the functional role of S100B in muscle tissue. Lastly, building on recent results pointing to S100B as to a molecular determinant of myoblast–brown adipocyte transition, we propose S100B as a transducer of the deleterious effects of accumulation of reactive oxygen species in myoblasts and, potentially, myofibers concurring to the pathophysiology of sarcopenia.